Financial Globalization and Monetary Policy - Devereux, Michael (IMF Working Papers; Working Paper ;, 2007)
What does financial globalization imply for the design of monetary policy? Does the case for price stability change in an environment of large cross country gross asset holdings?. This paper is concerned with the effects of monetary policy under endogenous international portfolio choice and incomplete markets. With endogenous portfolios, monetary policy takes on new importance due to its impact on the distribution of returns on nominal assets. Surprisingly, we find an even stronger case for price stability in this environment. Even without nominal rigidities, price stability has a welfare benefit by enhancing the risk sharing capacity of nominal bond returns.